The Optimum Design of Scanned Linear Antenna Array Using Sine Cosine Optimization Algorithm - Al hussein M. Alturfi; Sonia Goyal; Amrit Kaur (Wasit Journal of Computer and Mathematics Science, 2023)
In this article, the side lobe level (SLL) of the radiation pattern is reduced, and the first null beam width (FNBW) is kept constant by synthesizing symmetric scanning Linear Antenna Arrays (LAA), which is done by considering excitation amplitude as the optimization parameter. A Sine cosine algorithm (SCA) is used to achieve this objective. Three different case studies are illustrated in this article to show the effectiveness of SCA in LAA optimization. The results obtained show that the SCA algorithm performs better than Firefly Algorithm (FA), Symbiotic Organisms Search (SOS), and hybrid optimization algorithm based on Grasshopper Optimization Algorithm (GOA) and Antlion Optimization (ALO)